Determination of effective atomic number of multifunctional materials using backscattered beta particles – a novel method. Issue 2 (7th February 2020) - Hosamani, M. M.; Vinayak, A.; Mangeshkar, S.; Malode, S.; Bhajantri, S.; Hegde, V.; Hiremath, G. B.; Badiger, N. M.
Abstract: The effective atomic number of multifunctional composite materials has been determined experimentally by adopting backscattering of beta particles technique. A 2.2 MeV beta particles emitted from a weak radioactive beta source were allowed to backscatter at an angle of 150 degrees from the elemental and composite targets. The backscattered beta particles were detected with the end window Geiger–Mueller gas detector. Experimentally, it is observed that the yield of the backscattered beta particle increases with increasing the target thickness for pure elements. Then, the yield of backscattering beta particle saturates after a certain thickness. The linear fit between the saturated thickness and the atomic number of the elemental target has been used to determine the effective atomic number of composite materials. The determined Zeff values of multifunctional composite targets have been compared with the values obtained by Monte Carlo method and computational codes.